صيغ وضوابط استثمار أموال الوقف الحديثة (دراسة حالة الجزائر) (Journal of Economics and Management Research, 2020)
ملخص: إن العمل الخيري في الإسلام هو تعبير عن مقاصد الإسلام السامية التي تهدف إلى الإعمار في الأرض بأساليب متنوعة، وقد جسد الوقف الإسلامي هذا البعد الإنساني في أجلى صوره، بحيث ساهم في تحقيق التنمية وتحقيق أعلى عائد اقتصادي المجتمع إذا أحسن تنظيمها وتسييرها، وكذلك ساهم في الحد من المشاكل الاجتماعية. من هذا المنطلق اهتم علماء الإسلام به وبطرق تنميته بالبحث عن دليل مشروعيته من عموم نصوص الشريعة، كما قدم أيضا علماء الإسلام في ظل التطورات الإسلامية والنهضة الدينية والثقافية والاقتصادية للبلاد صيغ حديثة لاستثمار أموال الوقف على المستوى المحلي والإقليمي والدولي وذلك ليحافظ الوقف على وجوده واستمراره عبر التاريخ ومرور السنين. كما وضعوا أيضا ضوابط شرعية التي تحكم التعامل معها. Abstract: The philanthropic work in Islam is an expression of the supreme intentions of Islam that aim at reconstruction in the land in a variety of ways. The Islamic Endowment embodied this human dimension in its most visible form, so that it contributed to achieving development and achieving the highest economic return to society if it was well organized and managed, and also contributed In reducing social problems. From this standpoint, the scholars of Islam took an interest in it and the ways of its development by searching for evidence of its legitimacy from all the texts of Sharia. Islamic scholars also presented in the light of Islamic developments and the religious, cultural and economic revival of the country modern forms of investing endowment funds at the local, regional and international levels so that the endowment maintains its existence and its continuity throughout history And the years passed. They also established legal controls governing dealing with them.